Gambaran Kualitas Hidup Lansia Yang Tinggal Di Komunitas - Mila Nurkolila; Sugiharto Sugiharto (STIKes MERCUBAKTIJAYA, 2022)
Being older is an advanced stage of the life journey marked by a decrease in the body's ability to adapt to psychosocial problems and environmental stressors. The ability of the elderly to adapt to their conditions can affect their quality of life. Quality of life (QoL) is an individual's perception that is influenced by the cultural context and value system in which they live and in relation to goals, expectations, standards, and concerns. The study aims to describe the QoL of the elderly indwelling-community. The study applied a cross-sectional approach. Total sampling technique was used with inclusion criteria: the elderly who are registered as residents of Bugangan Village, aged >60 years old, and the elderly who are willing to be respondents. The Indonesian version of the WHOQOL-OLD questionnaire was used to assess respondents’ QoL. Data were analyzed using univariate analysis (mean and standard deviation). There are 151 elderlies participated in the study. The results showed that 52% respondents have a good quality of life. This may be related to the environmental-recognized and social activities that the elderly can still perform. Community nurses are recommended to provide more activities for elderly through POSYANDU LANSIA.